Attitude to the subject of chemistry in undergraduate nursing students at Fiji National University and Federation University, Australia. Issue 4 (December 2015) - Brown, Stephen; Wakeling, Lara; Peck, Blake; Naiker, Mani; Hill, Dolores; Naidu, Keshni
Summary: Attitude to the subject of chemistry was quantified in first-year undergraduate nursing students, at two geographically distinct universities. A purpose-designed diagnostic instrument (ASCI) was given to students at Federation University, Australia ( n = 114), and at Fiji National University, Fiji ( n = 160). Affective and cognitive sub-scales within ASCI showed reasonable internal consistency. Cronbach's α for the cognitive sub-scale was 0.786 and 0.630, and 0.787 and 0.788 for affective sub-scale for the Federation University and Fiji National University students, respectively. Mean (SD) score for the cognitive sub-scale was 10.5 (5.6) and 15.2 (4.1) for students at Federation University and Fiji National University, respectively ( P < 0.001, t -test). Mean (SD) score for the affective sub-scale was 13.1 (5.1) and 20.7 (4.3) for students at Federation University and Fiji National University, respectively ( P < 0.001, t -test). An exploratory factor analysis ( n = 274) confirmed a two-factor solution consistent with affective and cognitive sub-scales, each with good internal consistency. Quantifying attitude to chemistry in undergraduate nursing students using ASCI may have utility in assessing the impact of novel teaching strategies used in the education of nursing students in areas of bioscience and chemistry. However, geographically distinct populations of undergraduate nurses may show very different attitudes to chemistry.